PROBLEM OF CREATING OF COMPUTER-BASED MODEL OF ENVIRONMENT FOR TEACHERS’ IC COMPETENCE DEVELOPMENT (FOREIGN EXPERIENCE) - Nataliia V. Soroko (Information technologies and learning tools, 2013)
The paper describes the main approaches of domestic and foreign researchers to create computer-based learning environment. There are characterized popular models in the world of computer-based environment for adult education, which based on new information and communication technologies, such as Web 2.0, cloud-based technologies and other. There are selected the basic functions of computer-based environment in the educational process and for the development of teacher information and communication competence, as well as the requirements for creating a computer-based environment model for the development of teachers information and communication competence. It was determined that the combination of potential international strategic directions, information products and environments, participation of representatives of the educational community, particularly teachers and students in various projects, is an effective mechanism of development of the learning environment promoting the development of information and communication competence of the participants of the educational process.